Perceptions of Professionals, Faculty, and Students Regarding the Implementation of an Agricultural Communications Degree Program in the United Kingdom - Jefferson D. Miller; Abby Davis; Kobina D. Fanyinkah; Alex McLeod; Casandra Cox; K. Jill Rucker (Journal of International Agricultural and Extension Education, 2024)
The purpose of this study was to determine the perceptions of professionals, faculty, and students regarding the implementation of an agricultural communications degree program in the United Kingdom (U.K). It aimed to gather detailed opinions to aid in the planning of future agricultural communications curricula in the U.K., where no formal academic programs in this discipline exist in higher education. This study used a qualitative approach in the form of interviews to gain in-depth opinions on four different research objectives. Participants were pooled from three different demographic groups in the U.K: industry professionals, faculty, and students. These stakeholder expressed that writing and journalistic skills were extremely important for agricultural communications graduates to possess. Interpersonal skills were also useful. A generalized knowledge of agriculture was preferred. The study found that experiential learning placements would be a beneficial addition to a potential program, and those could be customized to fit the needs of the student. It also found that degree programs in the discipline would fit well into a bachelor’s or master’s program, or single modules could be integrated into existing programs in related disciplines. Recommendations of the study focused on the layout of a potential degree program. They also focused on conducting further research on potential placement opportunities and on the impact an agricultural communications degree program could have on females in agriculture.
Keywords: Agricultural communications; curriculum; academic program